Prosperity of Nepal Vs Security Forces of Nepal: Virgin Field of the Study - Paudel, Narendra Raj; Pahari, Srijana (Journal of APF Command and Staff College, 2019)
We analyze the prosperity of Nepal in relation to security forces of Nepal. The main argument discussed in this article is competent and committed security forces of Nepal contribute to foster and promote prosperity of Nepal. The prosperity of Nepal means the safeguarding sovereignty, territorial integrity, nationality, unity in diversity and maintaining law and order situation in the country. This can be achieved through development of security personnel, formulation of good policies which guides security forces and cultivation of favourable environment in the country. However, there are risk factors associated with this venture if not working properly.